The economics of fintech understanding digital transformation in financial services - Imerman, Michael B. (Cambridge, Massachusetts The MIT Press, 2025)
"An undergraduate/MBA textbook for the underserved market of courses on financial technologies and financial services"--
Includes bibliographical references and index.
Keywords: Economics; Financial services industry